Survey of load balancing techniques for Grid. (April 2016) - Patel, Deepak Kumar; Tripathy, Devashree; Tripathy, C.R.
Abstract: In recent days, due to the rapid technological advancements, the Grid computing has become an important area of research. Grid computing has emerged a new field, distinguished from conventional distributed computing. It focuses on large-scale resource sharing, innovative applications and in some cases, high-performance orientation. A Grid is a network of computational resources that may potentially span many continents. The Grid serves as a comprehensive and complete system for organizations by which the maximum utilization of resources is achieved. The load balancing is a process which involves the resource management and an effective load distribution among the resources. Therefore, it is considered to be very important in Grid systems. The proposed work presents an extensive survey of the existing load balancing techniques proposed so far. These techniques are applicable for various systems depending upon the needs of the computational Grid, the type of environment, resources, virtual organizations and job profile it is supposed to work with. Each of these models has its own merits and demerits which forms the subject matter of this survey. A detailed classification of various load balancing techniques based on different parameters has also been included in the survey. Highlights: Presents an extensive survey of the existing load balancing techniques proposed so far. The load balancing techniques have been appropriately classified under different headings. An analysis of trends in publication of load balancing techniques for Grid has been described.